PENGARUH KEMUDAHAN, KUALITAS LAYANAN, FITUR PRODUK TERHADAP KEPUASAN PENGGUNAAN MOBILE BANKING LIVIN BY MANDIRI (STUDI KASUS PT BANK MANDIRI KCP SUMBAWA BESAR): PENGARUH KEMUDAHAN, KUALITAS LAYANAN, FITUR PRODUK TERHADAP KEPUASAN PENGGUNAAN MOBILE BANKING LIVIN BY MANDIRI (STUDI KASUS PT BANK MANDIRI KCP SUMBAWA BESAR) - Hayat, Nahrul; Busman, Sherwin Ary (Program Studi Magister Manajemen Universitas Advent Indonesia, 2023)
This study aims to examine the Effect of Convenience, Service Quality and Product Features on Livin By Mandiri Mobile Banking User Satisfaction (Case Study of PT Bank Mandiri Kcp Sumbawa Besar). This study uses a quantitative method with an associative approach. Determination of the sample in this study using the Paul Leddy formula through non-probability sampling technique with purposive sampling method and obtained a total of 96 research samples. The data analysis technique in this study used multiple linear regression analysis and the analysis tool used was the application of the Statistical Program for Social Science (SPSS) 25 for Windows. The results of the analysis in this study showed that convenience did not have a significant effect while service quality partially had a positive effect and significant and product features partially have a positive and significant effect on user satisfaction